Online Worlds: Convergence of the Real and the Virtual - Bainbridge, William Sims.; SpringerLink (Online service) (London : Springer London, 2010)
Virtual worlds are persistent online computer-generated environments where people can interact, whether for work or play, in a manner comparable to the real world. The most popular current example is World of Warcraft, a massively multiplayer online game with eleven million subscribers. However, other virtual worlds, notably Second Life, are not games at all but internet-based collaboration contexts in which people can create virtual objects, simulated architecture, and working groups. This book brings together an international team of highly accomplished authors to examine the phenomena of virtual worlds, using a range of theories and methodologies to discover the principles that are making virtual worlds increasingly popular, and which are establishing them as a major sector of human-centred computing.
New World View -- Culture and Creativity: World of Warcraft Modding in China and the US -- The Diasporic Game Community: Trans-Ludic Cultures and Latitudinal Research Across Multiple Games and Virtual Worlds -- Science, Technology, and Reality in The Matrix Online and Tabula Rasa -- Spore: Assessment of the Science in an Evolution-Oriented Game -- Medulla: A Cyberinfrastructure-Enabled Framework for Research, Teaching, and Learning with Virtual Worlds -- A Virtual Mars -- Opening the Metaverse -- A Typology of Ethnographic Scales for Virtual Worlds -- Massively Multiplayer Online Games as Living Laboratories: Opportunities and Pitfalls -- Examining Player Anger in World of Warcraft -- Dude Looks like a Lady: Gender Swapping in an Online Game -- Virtual Doppelgangers: Psychological Effects of Avatars Who Ignore Their Owners -- Speaking in Character: Voice Communication in Virtual Worlds -- What People Talk About in Virtual Worlds -- Changing the Rules: Social Architectures in Virtual Worlds -- Game-Based Virtual Worlds as Decentralized Virtual Activity Systems -- When Virtual Worlds Expand -- Cooperation, Coordination, and Trust in Virtual Teams: Insights from Virtual Games -- Virtual Worlds for Virtual Organizing -- Future Evolution of Virtual Worlds as Communication Environments -- The Future of Virtual Worlds.
Keywords: Computer science; Computer graphics; Social sciences -- Data processing; Computer Science; User Interfaces and Human Computer Interaction; Computer Graphics; Computer Appl. in Social and Behavioral Sciences; Computers and Society; e-Commerce/e-business.